Phylogeography of High Mountain Caddisflies (Trichoptera) in Asias Subtropical Mountains - Deng, Xiling; Justus Liebig University Giessen (My University, 2023)
As one of the most prominent mountain systems on Earth, the Tibeto-Himalayan Region (THR), is not only famous for its geographic and climatic influence at a global scale but is also well-known for harboring high levels of biodiversity and it presently comprises two global biodiversity hotspots. To explain the formation of the rich biodiversity in this area, the “Mountain-Geobiodiversity Hypothesis (MGH)” proposes that the present-day montane biodiversity patterns are derived from a combination of geology, biology, and climate change. However, validations and refinements of the hypothesis for a broader taxonomic spectrum are missing, particularly from animals. Trichoptera, colloquially known as “caddisflies”, is the largest order of primary aquatic insects. Caddisflies occur on all continents except Antarctica and have adapted to virtually all forms of freshwater ecosystems, including high-altitude streams, rivers, and lakes. Caddisflies of the genus Himalopsyche (Rhyacophilidae) are mainly distributed in the subtropical mountains of central and eastern Asia. Currently, there are 56 named species within this genus: Twenty-three occur in the Himalayas, 34 in the Hengduan Mountains, and four species are distributed in both mountain systems. In addition, several species also occur in far east Asia and Southeast Asia, such as Indonesia and Japan, and one species inhabits North America. Hence, the Himalayas and Hengduan Mountains are the centers of diversity for this caddisfly group. The phylogenetic relationships of the genus Himalopsyche were recently resolved with traditional sequencing technology and morphology, but ambiguity remains about the shallow phylogeny of several species complexes. Also, studies of intraspecific variation and population genetics are hitherto lacking. Their high level of species diversity in subtropical mountains and the available knowledge of their phylogenetics and ecology make Himalopsyche a good model to study the formation of biodiversity of aquatic insects in these high mountain systems of Asia and assess the validity of the MGH. The central theme of this work is thus to derive hypotheses on the processes underlying the formation of the high biodiversity in these two mountain regions using selected caddisflies species of the genus Himalopsyche. Specifically, this work is focused on 1) solving the ambiguity of the shallow phylogeny of one Himalopsyche species complex; 2) studying intraspecific variation and population genetics of several Himalopsyche species. To address the open questions related to the evolutionary process, I harness the power and resolution of next-generation sequencing technologies including targeted amplicon sequencing, de novo sequencing, and whole genome resequencing. To assess the value of genomic-level data in resolving phylogenetic relationships in caddisflies, we reconstructed the phylogeny and performed gene flow and network analyzes on the hitherto unresolved H. martynovi complex using multiple allelic datasets generated from anchored hybrid enrichment (Chapter 1). The data identified three robust lineages, which were supported by morphological evidence. The remaining morphological ambiguity within H. martynovi sensu stricto may have resulted from gene flow within the species complex. I hypothesized this gene flow could have been fostered by climate oscillations and drainage re-arrangement. To verify the influence of climate and topography on species diversification, I attempted to investigate the intraspecific variation of Himalopsyche species by using genome-wide variants. A methodological study on how to set up a population genomic study regarding the impact of sequencing depth and relatedness of reference genomes is summarized in Chapter 2. In this technical chapter, I provided a general guideline for population genomic studies. I revealed that a high-quality reference genome closely related to the focal species would be optimal for setting up a population genomics study. In addition, the results of this study indicated that the population structure of H. tibetana and H. digitata were highly consistent with the geographic distribution of populations within the drainage and river networks. To further explore the formation of the diversity of Himalopsyche, especially in different mountain regions, I then conducted a comparative phylogeographic study (Chapter 3). In this study, I performed a series of population genomic inferences using individual-based genomic data on four Himalopsyche species that inhabit different niches in the Himalayas and the Hengduan Mountains. The population genetic patterns of the four species demonstrated that the high-elevation species showed strong local differentiation in both mountain regions. In contrast, the low-elevation species were shaped by river basins, indicating greater regional dispersal activity. In addition, caddisfly species in the Himalayas generally exhibited an East-West oriented dispersal. Species from the Hengduan Mountains showed greater connectivity on the North-South orientation, suggesting that species have a higher chance to survive in the Hengduan Mountains by both in-situ displacement (along the elevational gradients) and long-distance dispersal (along the latitudinal gradients) during glaciation. To better understand the processes underlying these differences in the context of historical climate and topography, I incorporated genomic and ecological evidence to reveal the demographic history and potential habitat range dating back to the last glacial maximum. These analyzes revealed a demographic expansion for all four Himalopsyche species linked to increased potential habitats during the LGM. Therefore, this study demonstrated that historical geodiversity and climate fluctuations interact and influence the diversification of caddisflies in the THR, thus supporting the MGH.
Keywords: caddisfly; mountain biodiversity; Tibeto-Himalayan Region; Phylogeography; genomics; Next Generation Sequencing; evolution; ddc:570